Montreal Cognitive Assessment Is Superior to Standardized Mini-Mental Status Exam in Detecting Mild Cognitive Impairment in the Middle-Aged and Elderly Patients with Type 2 Diabetes Mellitus. (11th July 2013) - Alagiakrishnan, Kannayiram; Zhao, Nancy; Mereu, Laurie; Senior, Peter; Senthilselvan, Ambikaipakan
Abstract : Aim . This study compares the usefulness of Montreal Cognitive Assessment (MoCA) to Standardized Mini-Mental Status Exam (SMMSE) for diagnosing mild cognitive impairment (MCI) in Type 2 diabetes mellitus (DM) population. Methods . This prospective pilot study enrolled 30 community dwelling adults with Type 2 DM aged 50 years and above. Subjects were assessed using both the SMMSE and MoCA for MCI. In all subjects, depression and dementia were ruled out using the DSM IV criteria, and a functional assessment was done. MCI was diagnosed using the standard test, the European consortium criteria. Sensitivity and specificity analysis, positive and negative predictive values, likelihood ratios and Kappa statistic were calculated. Results . In comparison to consortium criteria, the sensitivity and specificity of MoCA were 67% and 93% in identifying individuals with MCI, and SMMSE were 13% and 93%, respectively. The positive and negative predictive values for MoCA were 84% and 56%, and for SMMSE were 66% and 51%, respectively. Kappa statistics showed moderate agreement between MoCA and consortium criteria (kappa = 0.4) and a low agreement between SMMSE and consortium criteria (kappa = 0.07). Conclusion . In this pilot study, MoCA appears to be a better screening tool than SMMSE for MCI in the diabetic population.